Turbulence dissipation & its induced entrainment in subsonic swirling steam injected in cocurrent flowing water - Khan, Afrasyab; Mohd Sobri, Takriff; Masli Irwan, Rosli; Nur Tantiyani, Ali Othman; Khairuddin, Sanaullah; Andrew Ragai, Henry Rigit; Ajmal, Shah; Atta, Ullah; Muhammad Umar, Mushtaq (Elsevier Ltd., 2019)
Subsonic swirling steam induced turbulence, its dissipation, and entrainment inside the concurrent flowing water has been investigated on an experimental basis. Pressure fluctuations of dissimilar amplitudes have been observed which have been attributed to the vortices and hence instances for entrainment on a spatial basis. The extent of turbulence dissipation has been measured by the rate of decrement of the smallest pressure fluctuation of amplitude 0.04 bars. It has been observed that the turbulence dissipation along radial direction rises from 2.3 to 6.3 fluctuations/cm with rising in the inlet pressure of steam & till 12.5 fluctuations/cm in case of rising in rpm of the swirler. On a temporal scale, the turbulence dissipation varies from 0.7 fluctuations/sec at initial conditions which rise till 1.9 fluctuations/sec with the rise in inlet pressure of steam & 3.7 fluctuations/sec in case of rising in rpm of the swirler. Effect of rising in compressibility & rpm on sheer layer transformation into vortices imparted in terms of spatial dislocation along the axial axis, which ranges from 64–66% to 35–41% respectively. The extent of entrainment has found to be influenced by an increase in the compressibility, the rpm of the swirler and the surrounding water inlet pressure, which has been represented by the number of occurrences of the vortices across radial and axial directions. Effects imparted by the given conditions on fluctuations, entrainment, and non-dimensionalized flux has also been investigated.